The Core Stem Genes SOX2, POU5F1/OCT4, and NANOG Are Expressed in Human Parathyroid Tumors and Modulated by MEN1, YAP1, and β-catenin Pathways Activation - Chiara Verdelli; Annamaria Morotti; Giulia Stefania Tavanti; Rosamaria Silipigni; Silvana Guerneri; Stefano Ferrero; Leonardo Vicentini; Valentina Vaira; Sabrina Corbetta (Biomedicines, 2021)
Tumors of the parathyroid glands are the second most common endocrine neoplasia. Epigenetic studies revealed an embryonic signature involved in parathyroid tumorigenesis. Here, we investigated the expression of the stem core genes SOX2, POU5F1/OCT4, and NANOG. Rare cells within normal parathyroid glands expressed POU5F1/OCT4 and NANOG, while SOX2 was undetectable. Nuclear SOX2 expression was detectable in 18% of parathyroid adenomas (PAds, n = 34) involving 5–30% of cells, while OCT4 and NANOG were expressed at the nuclear level in a more consistent subset of PAds involving 15–40% of cells. Most parathyroid carcinomas expressed the core stem genes. SOX2-expressing cells co-expressed parathormone (PTH). In PAds-derived primary cultures, silencing of the tumor suppressor gene MEN1 induced the expression of SOX2, likely through a MEN1/HAR1B/SOX2 axis, while calcium-sensing receptor activation increased SOX2 mRNA levels through YAP1 activation. In addition, inducing nuclear β-catenin accumulation in PAds-derived primary cultures by short-term incubation with lithium chloride (LiCl), SOX2 and POU5F1/OCT4 expression levels increased, while NANOG transcripts were reduced, and LiCl long-term incubation induced an opposite pattern of gene expression. In conclusion, detection of the core stem genes in parathyroid tumors supports their embryogenic signature, which is modulated by crucial genes involved in parathyroid tumorigenesis.